Telling Stories from the Field: Children and the Politics of Ethnographic Representation - Caputo, Virginia (Anthropologica, 2022)
Bringing a feminist lens to bear on the study of children and childhood has progressed at a slow pace since the mid-1980s. Despite repeated calls for a broader engagement between feminism and childhood studies, the links between the two areas of study remain weak. This article aims to address this gap by examining the processes in which "truths" about children's gendered lives are produced. Drawing from fieldwork in an urban Canadian location, I argue that within the structure of adult beliefs and practices regarding what boys and girls "ought to be," children create spaces in which they are able to "play" with, resist, accommodate, refuse and create alternatives to such beliefs and practices. Based on my research, I explore the ways "violence" is one strategy used by children to create spaces for competing discourses of childhood to emerge. I conclude by reflecting on the implications of using a feminist lens for understanding childhood, maintaining that power plays itself out everyday in children's lives in largely invisible yet compelling ways